The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ijid.2021.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium and Vitamin D levels: Correlation with severity of COVID-19 in hospitalized patients in Royal Hospital, Oman

Abstract: Introduction There have been studies revealing hypocalcemia in severe covid-19 and low vitamin D levels that warranted further studies. Objective Our study investigates the correlation between calcium levels at presentation as a primary endpoint, and pre-existing calcium levels as a secondary endpoint, to severity of disease presentation and progression. Method Observational cohort study in adults admitted with COVID-19 from March till Septem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 65 publications
1
28
0
5
Order By: Relevance
“…A recent study reported that serum calcium and vitamin D levels in COVID-19 patients were lower than in healthy individuals [43]. Osman et al showed that hypocalcemic COVID-19 patients had longer hospitalization duration and higher severity of the disease, yet they could not find a link between vitamin D status and COVID-19 [44]. Our results showed that the Ca 2+ level of cases was relatively increased on the 7th and day after treatment, yet it was not statistically significant It is known that vitamin D acts as a regulator of many cytokines in many cell types of the immune system and in many diseases [11,[19][20][21].…”
Section: Vitamin D and Covid-19mentioning
confidence: 98%
“…A recent study reported that serum calcium and vitamin D levels in COVID-19 patients were lower than in healthy individuals [43]. Osman et al showed that hypocalcemic COVID-19 patients had longer hospitalization duration and higher severity of the disease, yet they could not find a link between vitamin D status and COVID-19 [44]. Our results showed that the Ca 2+ level of cases was relatively increased on the 7th and day after treatment, yet it was not statistically significant It is known that vitamin D acts as a regulator of many cytokines in many cell types of the immune system and in many diseases [11,[19][20][21].…”
Section: Vitamin D and Covid-19mentioning
confidence: 98%
“…Others have found associations between vitamin D sufficiency and reduced incidence of COVID-19, but not in outcomes after infection [ 155 , 158 ]. However, some studies have reported contrary, negative results [ 143 , 144 , 147 ]. Overall, the evidence supports the importance of the relationship between vitamin D and COVID-19, a relationship that requires continued investigation by means of large-scale, nationally representative studies.…”
Section: Vitamin D and Covid-19: Summary Of The Evidencementioning
confidence: 99%
“…Hypocalcemia was seen in 68.8% of the patients. Patients with hypocalcemia needed a significantly longer duration of hospitalization and required more high-dependency unit (HDU)/ICU admissions than those without hypocalcemia ( 61 ). Nevertheless, a high frequency of asymptomatic hypocalcemia (and hypophosphatemia) has also been reported in non-severe COVID-19 patients, the clinical relevance of which remains uncertain ( 62 ).…”
Section: Introductionmentioning
confidence: 99%